Kreativitas guru dalam meningkatkan hasil belajar siswa pada mata pelajaran PPKn di SMP Kristen Getsemani Sario Kota Baru Manado - Ganna, Margu Sanda; Biringan, Julien; Wua, Telly Delly (Jurnal Pendidikan Kewarganegaraan dan Politik, 2025)
This study will examine how teacher innovation can improve student learning outcomes in the subject of Pancasila and Citizenship Education (PPKn) at SMP Kristen Getsemani Sario Kota Baru Manado. The research approach used is descriptive qualitative, with data collection through observation, interviews, and documentation. The subjects of the study were the principal, PPKn teachers, and students. The results of the study indicate that instructor innovation in PPKn learning is very important for improving student learning outcomes. Teachers use a variety of innovative approaches to increase student participation, including group discussions, project-based learning (PjBL), and debates. Furthermore, research has shown that the use of digital learning media such as educational videos, infographics, and interactive simulations can help students understand abstract concepts in PPKn. These findings are consistent with Vygotsky's social learning theory and Bloom's idea of ​​three domains in education, as well as the domains that must be met in terms of cognitive, emotional, and psychomotor skills to create student competence and dramatically improve learning outcomes.